Clinical utility of intraoperative electrocorticography for epilepsy surgery: A systematic review and meta‐analysis. Issue 2 (12th December 2022) - Goel, Keshav; Pek, Valérie; Shlobin, Nathan A.; Chen, Jia‐Shu; Wang, Andrew; Ibrahim, George M.; Hadjinicolaou, Aristides; Roessler, Karl; Dudley, Roy W.; Nguyen, Dang K.; El‐Tahry, Riëm; Fallah, Aria; et al.
Abstract: Despite the widespread use of intraoperative electrocorticography (iECoG) during resective epilepsy surgery, there are conflicting data on its overall efficacy and inability to predict benefit per pathology. Given the heterogeneity of iECoG use in resective epilepsy surgery, it is important to assess the utility of interictal‐based iECoG. This individual patient data (IPD) meta‐analysis seeks to identify the benefit of iECoG during resective epilepsy surgery in achieving seizure freedom for various pathologies. Embase, Scopus, and PubMed were searched from inception to January 31, 2021 using the following terms: "ecog", "electrocorticography", and "epilepsy". Articles were included if they reported seizure freedom at ≥12‐month follow‐up in cohorts with and without iECoG for epilepsy surgery. Non‐English articles, noncomparative iECoG cohorts, and studies with <10% iECoG use were excluded. This meta‐analysis followed the PRISMA 2020 guidelines. The primary outcome was seizure freedom at last follow‐up and time to seizure recurrence, if applicable. Forest plots with random effects modeling assessed the relationship between iECoG use and seizure freedom. Cox regression of IPD was performed to identify predictors of longer duration of seizure freedom. Kaplan–Meier curves with log‐rank test were created to visualize differences in time to seizure recurrence. Of 7504 articles identified, 18 were included for study‐level analysis. iECoG was not associated with higher seizure freedom at the study level (relative risk = 1.09, 95% confidence interval [CI] = 0.96–1.23, p  = .19, I 2  = 64%), but on IPD ( n  = 7 studies, 231 patients) iECoG use was independently associated with more favorable seizure outcomes (hazard ratio = 0.47, 95% CI = .23–.95, p  = .037). In Kaplan–Meier analysis of specific pathologies, iECoG use was significantly associated with longer seizure freedom only for focal cortical dysplasia (FCD; p  < .001) etiology. Number needed to treat for iECoG was 8.8, and for iECoG in FCD it was 4.7. We show iECoG seizure freedom is not achieved uniformly across centers. iECoG is particularly beneficial for FCD etiology in improving seizure freedom.